Late Feyerabend on materialism, mysticism, and religion. (June 2016) - Martin, Eric C.
Abstract: Feyerabend's interests in religion and mysticism grew through his career. In his later writings, Feyerabend's numerous critiques of scientific materialism are often accompanied by purported advantages of religious orientations and temperaments. These recommendations do not simply follow from his tolerant theoretical pluralism; they are more positive attempts to articulate distinctive aspects of human life satisfied by religion, but not by scientific materialism. Elevating the human need for mystery, reverence, and love, he contrasts these goods with the deliverances of monistic conceptions of science and reason. I bring attention to some of the common themes in these remarks to argue that they were integral with other parts of his philosophical project and that they could serve as helpful rejoinders to contemporary exhortations to science-based secularism from philosophers of science. Highlights: Feyerabend's interests in religion and mysticism grew through his career. In his later writings, Feyerabend's numerous critiques of scientific materialism are often accompanied by purported advantages of religious orientations and temperaments. This paper highlights Feyerabend's scattered remarks on aspects of human life left unsatisfied by certain monistic conceptions of science and reason. Feyerabend's ideas can serve as helpful rejoinders to contemporary exhortations to science-based secularism.